PENGARUH UKURAN ATOMISASI BAHAN BAKAR TERHADAP UNJUK KERJA MOTOR BAKAR - Abrar Riza; Hansel Hansel; Harto Tanujaya (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: The size of droplet affects the evaporation of the fuel. The greater the size of droplet is also the energy of fuel evaporation. The evaporation energy is directly proportional to the size of the droplet and oxidation must be mixed homogeneously. Mixing conditions in the combustion process affect the rate of combustion. One of the conditions of combustion is the droplet to the vapor. The more perfect the evaporation process the better the combustion process. This study saw the success of combustion due to the size of droplet on the performance. The droplet produced by atomization in the form of liquid granules. The size of atomization is the determinant of burning success. The four-stroke Otto engine performance depends on the size of the atomization in order to mix well with the oxidant during combustion process. The results of the research characteristic of the machine are due to the influence of the size of the droplet seen from the generated power, torque and thermal efficiency. Characteristic features increase with decreasing the size of the droplet. Torque increased 7.9%, power generated increased 7%, and thermal efficiency increased up to 7.3%. The results of this study show size of the droplet can improve the performance of engine.